A chat with Dr. Birama Sidibe, Founder of Agrobiotech, Mali (Episode 3) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this episode, Dr Sidibe talks about Agribiotech has faced while trying to combat food insecurity in Mali and its environs.